Predisposition of connotatively marked units to metaphors - Gulnoza Narziyeva (Zien Journals, 2024)
This article examines the semantic-stylistic meaning of phraseological units of the connotative aspect, since we consider connotation as emotional, evaluative, expressive and functional-stylistic components of a usual and occasional nature, which are part of the meaning of a linguistic unit.
Keywords: phraseological unit; connotative aspect; metaphorical phrases; expressiveness